2022
DOI: 10.7759/cureus.26419
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Impact of Anxiety With Migraines: A Narrative Review

Abstract: Migraine is a chronic, disabling neurological disorder characterized by recurrent episodes of headache. Psychiatric disorders have been reported to arise due to a patient's physical and emotional stress caused by migraine episodes, with anxiety disorders being one of the most commonly associated psychiatric disorder with migraine. This association poses the question of similar or shared pathogenesis between the two disorders and raises a concern for the diagnosis and management of situations when these disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Individuals with and without anxiety had comparable prevalence rates of migraine, tension headache, and other types. These results contrast with a previous study by Kumar et al, which identified a positive association between anxiety and migraine [ 34 ]. This might be due to differences in the assessment of anxiety or sample characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Individuals with and without anxiety had comparable prevalence rates of migraine, tension headache, and other types. These results contrast with a previous study by Kumar et al, which identified a positive association between anxiety and migraine [ 34 ]. This might be due to differences in the assessment of anxiety or sample characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are similar to associations previously found between symptom patterns in CRS and mood disorders, 29 although comorbid migraine appears to have a significantly stronger effect size on QOL. Nevertheless, these results also illustrate the known general relationship between migraine and mood disorders in the setting of CRS 30–32 …”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, these results also illustrate the known general relationship between migraine and mood disorders in the setting of CRS. [30][31][32] These results have important implications for guiding clinical suspicions of comorbid migraine in these patients and influencing further studies on the pathophysiology behind the high prevalence of migraine in CRS patients. Given the negative association between nasal polyps and migraine in CRS, there may be utility in endotyping for CRS patients with migraine.…”
Section: Discussionmentioning
confidence: 89%
“…It is also proven that individuals with prolonged migraine are more likely to experience psychiatric comorbidity than those with episodic migraine [6]. The research findings are consistent and demonstrate a higher chance of developing depression, bipolar disorders, a broad range of anxiety disorders, and posttraumatic stress disorder [7].…”
Section: Reviewsupporting
confidence: 52%